Atenolol and infantile hemangioma. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2016)
The discovery of the pediatric dermatology school of Bordeaux regarding the efficacy of propranolol, a nonselective beta-blocker, on infantile hemangioma (IH) was revolutionary because it has changed the problematic IH therapy, has significantly improved the efficacy / side effect relationship in this disorder thus allowing to extend the treatment to IH responsible for esthetic and psychosocial damage, and has stimulated research on antiangiogenic drugs also in other fields such as retinopathy of prematurity and carcinogenesis. (...).